Electrochemical characterization of iron oxide composite electrode for degradation of Oxytetracycline compounds - Kamarudin, Nor Khalidah (2019)
In developed countries, pharmaceutical compounds are often use in the hospitality and veterinary. The ability of pharmaceutical compounds in livestock make the usage unstoppable. The compounds were made to fit the need of the patient. In modern agricultural also, the compounds were used for breeding and developing of animal growth. A large amount of the pharmaceutical compounds had been found in the soils, surface waters, ground waters and drinking waters even at low concentration in the environment. The pharmaceutical compounds can be among these compounds, it shows that antibiotics are the most often and highest concentration that have been detected in the seawater sample. The presence of the antibiotic in water may be due to the daily activities used by the hospitality and veterinary. Oxytetracycline is one of the antibiotic compounds where the compounds had causing a rise issues towards the environment. The excessive amount of oxytetracycline in water could cause diseases that cannot be treated with pharmacotherapy. Thus, cyclic voltammetry test was carried out to characterize iron oxide composite as electrode for electrochemical degradation of oxytetracycline (OTC) compounds in 0.5M hydrochloride acid (HCl), 0.5M sodium hydroxide (NaOH) and 0.5M sodium chloride (NaCl). Comparison degradation of oxytetracycline compounds were investigated to select the optimum operating condition. As results, the best electrochemical degradation of OTC by using iron oxide composite electrode was observed in 0.5M HCl without the presence of carbon black at applied potential range from -0.5V to 2.0V.